Sistem Pendukung Keputusan Untuk Meningkatkan Efektivitas Dalam Pembayaran Pajak Bumi Dan Bangunan Di Badan Pendapatan Daerah Kabupaten Seluma - Rama Amandika; Pahrizal Pahrizal; Yulia Darnita; Muntahanah Muntahanah (Jurnal Media Infotama, 2024)
The increasing development of computer technology has an impact on various fields. Including land and building taxes. Determination of property tax which was done manually has gradually developed using computers. Along with this, mapping technology is also developing rapidly. Therefore, integration between taxpayer data and mapping data is very important for each individual. A Decision Support System is a computer-based information system that takes an approach to generating various decision alternatives to help certain parties in dealing with problems using data and models. The proposed method is Analytic Hierarchy Process (AHP) which is a method that is able to create a sequence of alternative decisions and select the best alternative in a decision support system to increase effectiveness in paying building taxes. AHP allows judgment and decision making based on uncertain and insignificant data. By using the AHP method, hopefully it can help make decisions easier in increasing the effectiveness of land and building tax payments at the Seluma Regency Revenue Agency Service. The decision support system application to increase effectiveness in paying land and building taxes in the regional revenue agency of Seluma district was successfully built using the Analytic Hierarchy Process (AHP) method. Incremental research methods can be applied for application development. Application testing was carried out using the Blackcox method and the results the application is declared suitable for implementation.Keywords: SPK, Property TAX, AHP